Are Dual Enrollment Students College Ready? Evidence from the Wabash National Study of Liberal Arts Education - An, Brian P.; Taylor, Jason L. (Education Policy Analysis Archives, 2015)
We examine whether dual enrolled students display greater levels of college readiness than nonparticipants. Advocates assert that dual enrollment improves students’ college readiness, but despite these assertions, few researchers have evaluated this relationship. Moreover, researchers that do consider whether dual enrollment improves college readiness examine this relationship while students participate in dual enrollment or shortly thereafter. Unlike traditional measures of college readiness that tend to emphasize the cognitive domain of college readiness, we use measures that integrate both cognitive and noncognitive domains of college readiness. We find that students who participated in dual enrollment tend to be more college ready than those who did not earn college credit in high school. The exception is that there is no statistical difference between dual enrollees and non-accelerators in their key transition knowledge and skills. The magnitude of the dual enrollment effect is second only to gender.